THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL MANAGEMENT ON THE PERFORMANCE OF SMEs IN MAKASSAR CITY - Ridha Farha Aditia; Muhammad Ali; Julius Jilbert (Paulus Journal of Accounting (PJA), 2023)
This study aims to evaluate the effect of Financial Literacy and financial management on the performance of Micro, Small and Medium Enterprises (MSMEs) in Makassar City. The population of this study is all MSMEs in which are registered with the Cooperatives and Micro, Small and Medium Enterprises Office of Makassar City, with a total number of MSMEs that are still active in 2021 as many as 715 businesses. The sample selection was carried out using the Purposive Sampling technique, namely selecting samples based on consideration certain. Data collection in this study was carried out through questionnaires and documentation. The collected data were analyzed using descriptive quantitative analysis methods, instrument tests (validity and reliability), classical assumptions, and hypothesis testing which included simple regression, t test, and partial coefficient of determination (r2). The results showed that financial literacy partially had an effect positive and significant impact on MSME financial management in Makassar City. This means that a good understanding of financial literacy can contribute to improving more effective financial management for MSMEs in Makassar City.